Alternativa de inversiones por parte del sector público para mejorar el bienestar social del sector Venus del río Quevedo cantón Quevedo año 2012 - Velásquez Haro, Josehp Enmanuel (2013)
The present investigation I analyze " ALTERNATIVE OF INVESTMENTS ON THE PART OF THE PUBLIC SECTOR TO IMPROVE THE SOCIAL WELL-BEING OF THE SECTOR " VENUS OF THE RIVER QUEVEDO " CANTON QUEVEDO YEAR 2012 - 2013 " in the same one that detected to itself that in the cooperative it does not exist the necessary works for well basic infrastructure lives with regard to sanitary works through networks of electric power center of health, park recreacionales etc. In general terms, significant advances have been obtained as for the extension of the coverage of basic services of health, sidewalks and bordillos, paving, electric power, schools. The municipal government has come implementing a series of initiative and projects in order improving the efficiency of the works realized in the sector Venus of the river Quevedo, the process has been sequential, still it does not include the totality of the services in the inhabitants, being obvious that much is absent for doing. It is indispensable to shape a frame orientador and of integration on initiatives of priority works in the parish venus of the river Quevedo that there allows to raise the well-being economic partner of his inhabitants. To implement mechanism and instruments that there demonstrates the need of a culture of management in the public sector, which the commitment promotes the participation and accelerates the implantation of works and generate a positive short-term impact and promote the change of culture in the public sector.